Study on the concrete beam depth reduction using steel fibre under flexural load - Hoo, Zi Hao (2015)
Nowadays, the construction of high rise building was gradually increased as the demand of property increase. Construction of high rise building required large structural components to support the load. Therefore, the deep beam of the building will decrease the space of the interior building and not economically efficient because reduce the space of building. The experimental work presented herein was aimed to study on the concrete beam depth reduction by using steel fibre under flexural load. The hooked end steel fibres with aspect ratio of 80 were used. The dosage of steel fibres in concrete mix was based on the volume fraction of Vf = 0.4% (30kg/m3). There were three tests such as compressive test, flexural test and modulus of elasticity carried out in this research. In order to determine the mechanical properties of the specimens, a total of 6 cylinders concrete which divided into 3 control cylinder, Vf = 0 % and 3 steel fibre cylinders and a total of 49 beams with different depth were casted. The dimension of the beam were 100mm for width and 500mm for length while the depth of steel fibre reinforced concrete (SFRC) beam various from 50mm, 60mm, 70mm, 80mm, 90mm, 100mm and 100mm of control beam which was plain concrete, Vf = 0%. Each of the depth casted for 7 beams. The dimension of cylinder concrete with 110mm in diameter and 200mm in height. The results indicate that the compressive strength of SFRC increase about 27.66% compared to the control specimen. Meanwhile, the concrete which included steel fibre highly enhanced the flexural of SFRC. The load for depths of 100mm SFRC beams was able to exceed all of the control beam while the 90mm depth of SFRC beams able to reach the load of the control beams. The result of modulus of elasticity was increased compare to control specimen. In conclusion, SFRC beam include steel fibre able to increase the compressive strength, flexural strength and modulus of elasticity.